Competency management in Slovenia: Paradoxes between development trends and drivers of change - Jürgen Mühlbacher; Michaela Nettekoven; Jure Kovac (Journal for East European Management Studies, 2011)
The focus of the transitional processes in CEE studies has changed in recent years. One important study area in the transitional processes in CEE is the construction of a globally competitive economy structure and increased efficiency of the rule of law. An important element of the competitiveness of companies is individual competency management. Especially in transition economies like Slovenia, human resources have to be regarded as a key factor for the current and future success of the economy. This article presents the study results that include managers' opinions regarding the connections between the external and internal drivers of change and influencing competency management in Slovenia. – – In den letzten Jahren hat sich der Schwerpunkt bei der Erforschung der Transitionsprozesse in MOE geändert. Im Vordergrund stehen nicht mehr Studien zur Transformation in eine Marktwirtschaft, sondern die Konstruktion einer global wettbewerbsfähigen Wirtschaftstruktur und die Umsetzung eines Rechtsstaates nach europäischem Muster. Ein wichtiges Element der Wettbewerbsfähigkeit von Unternehmen ist das individuelle Kompetenzmanagement. Insbesondere in Transitionsökonomien wie Slowenien müssen die Arbeitskräfte als ein Schlüsselfaktor für den gegenwärtigen und den zukünftigen Erfolg einer Wirtschaftskraft betrachtet werden. Im Beitrag werden Forschungsergebnisse vorgestellt, die den Standpunkt von Managern im Zusammenhang mit externen und internen Treibern der Veränderungen vorstellen sowie deren Einfluss auf das Kompetenzmanagement in Slowenien.
Keywords: 650; Competency management; human resources; transition economies; Slovenia